A homozygous splice site mutation in SLC25A42, encoding the mitochondrial transporter of coenzyme a, causes metabolic crises and epileptic encephalopathy - Iuso, Arcangela; Alhaddad, Bader; Weigel, Corina; Kotzaeridou, Urania; Mastantuono, Elisa; Schwarzmayr, Thomas; Graf, Elisabeth; Terrile, Caterina; Prokisch, Holger; Strom, Tim M.; Hoffmann, Georg F.; Meitinger, Thomas; et al. (Springer, 2019)
SLC25A42 is an inner mitochondrial membrane protein which has been shown to transport coenzyme A through a lipid bilayer in vitro. A homozygous missense variant in this gene has been recently reported in 13 subjects of Arab descent presenting with mitochondriopathy with variable clinical manifestations. By exome sequencing, we identified two additional individuals carrying rare variants in this gene. One subject was found to carry the previously reported missense variant in homozygous state, while the second subject carried a homozygous canonical splice site variant resulting in a splice defect. With the identification of two additional cases, we corroborate the association between rare variants in SLC25A42 and a clinical presentation characterized by myopathy, developmental delay, lactic acidosis, and encephalopathy. Furthermore, we highlight the biochemical consequences of the splice defect by measuring a mild decrease of coenzyme A content in SLC25A42-mutant fibroblasts.
CRIS-Team Scopus Importer:2019-05-07

Collaborative evaluation study on 18 candidate diseases for newborn screening in 1.77 million samples - Maier, Esther M.; Mütze, Ulrike; Janzen, Nils; Steuerwald, Ulrike; Nennstiel, Uta; Odenwald, Birgit; Schuhmann, Elfriede; Lotz-Havla, Amelie S.; Weiss, Katharina J.; Hammersen, Johanna; Weigel, Corina; Thimm, Eva; et al. (Journal of Inherited Metabolic Disease, 2023)
Analytical and therapeutic innovations led to a continuous but variable extension of newborn screening (NBS) programmes worldwide. Every extension requires a careful evaluation of feasibility, diagnostic (process) quality and possible health benefits to balance benefits and limitations. The aim of this study was to evaluate the suitability of 18 candidate diseases for inclusion in NBS programmes. Utilising tandem mass spectrometry as well as establishing specific diagnostic pathways with second-tier analyses, three German NBS centres designed and conducted an evaluation study for 18 candidate diseases, all of them inherited metabolic diseases. In total, 1 777 264 NBS samples were analysed. Overall, 441 positive NBS results were reported resulting in 68 confirmed diagnoses, 373 false-positive cases and an estimated cumulative prevalence of approximately 1 in 26 000 newborns. The positive predictive value ranged from 0.07 (carnitine transporter defect) to 0.67 (HMG-CoA lyase deficiency). Three individuals were missed and 14 individuals (21%) developed symptoms before the positive NBS results were reported. The majority of tested candidate diseases were found to be suitable for inclusion in NBS programmes, while multiple acyl-CoA dehydrogenase deficiency, isolated methylmalonic acidurias, propionic acidemia and malonyl-CoA decarboxylase deficiency showed some and carnitine transporter defect significant limitations. Evaluation studies are an important tool to assess the potential benefits and limitations of expanding NBS programmes to new diseases.
CRIS-Team Scopus Importer:2023-09-22
Keywords: dried blood spot; evaluation study; Germany; inborn errors of metabolism; newborn screening; public health; tandem mass spectrometry

Congenital disorders of glycosylation with defective fucosylation - Huellen, Andreas; Falkenstein, Kristina; Weigel, Corina; Huidekoper, Hidde; Naumann-Bartsch, Nora; Spenger, Johannes; Feichtinger, Rene G.; Schaefers, Jacqueline; Frenz, Stephanie; Kotlarz, Daniel; Momen, Tooba; Khoshnevisan, Razieh; et al. (Journal of Inherited Metabolic Disease, 2021)
Fucosylation is essential for intercellular and intracellular recognition, cell-cell interaction, fertilization, and inflammatory processes. Only five types of congenital disorders of glycosylation (CDG) related to an impaired fucosylation have been described to date: FUT8-CDG, FCSK-CDG, POFUT1-CDG SLC35C1-CDG, and the only recently described GFUS-CDG. This review summarizes the clinical findings of all hitherto known 25 patients affected with those defects with regard to their pathophysiology and genotype. In addition, we describe five new patients with novel variants in the SLC35C1 gene. Furthermore, we discuss the efficacy of fucose therapy approaches within the different defects.
CRIS-Team Scopus Importer:2021-09-24
Keywords: CDG; coarse facial features; developmental delay; epilepsy; fucosylation; intellectual disability; neutrophilia